Ursos, filhotes e caçadores: cultura, identidade e virilidade “Bear” paulista - Flauaus, Vinicius Melo (2019)
This research proposes a historical perspective of analysis of the culture of the Bear Community, focusing on the city of São Paulo, being that an unfolding of the homossexual subcultures that has as characteristic the valorization of the fat body, hair and beard in different aesthetic subclassifications, performances and expectations on that body. Knowing that there is a culture with an iconographic set, a discursive set and own socialization environments, the research cross results of previous researches, interviews with the community's members and graphic materials (as the Bear + Magazine and advertising of parties focused on “Bear public”) with the initial objective to raise the history and that community's cultural production in São Paulo. And, in a second moment, to analyze the representations about the body and the virility of those bears